Book review: Holistic Special Education: Camphill Principles and Practice. Robin Jackson, editor - Jeremy Millar (Scottish Journal of Residential Child Care)
Living in the pressurised, information-overloaded and, often, fearful times that typify the beginning of the 21st century, it can be hard to step back and reconnect with that which we know to be authentic, meaningful and life promoting. This book offers the reader just that opportunity. Holistic Special Education: Camphill Principles and Practice is a story of a vision transcending the destruction and displacement of the Nazi era, and then bringing a holistic philosophical and spiritual approach to the care of children with special needs in the North East of Scotland. This approach is manifest at the Camphill school/community, which practises curative education developed from the philosophy of the anthroposophical work of Rudolph Steiner.